Prolonged-release opioid agonist therapy: qualitative study exploring patients' views of 1-week, 1-month, and 6-month buprenorphine formulations - Joanne Neale; Charlotte N. E. Tompkins; John Strang (BMC, 2019)
Abstract Background Options for opioid agonist therapy (OAT) are expanding with the development of prolonged-release (also known as extended-release) 1-week, 1-month, and 6-month formulations of buprenorphine. There is an assumption that patients will welcome these new treatments and medication adherence will correspondingly increase. However, there has been little research exploring patients' views of prolonged-release buprenorphine. This paper aims to understand which durations patients prefer and why, and to consider the findings with reference to the development of future OAT products. Methods Data were generated as part of a qualitative interview study. Fieldwork was conducted in London, UK, during 2018 (before any prolonged-release OAT formulations were licensed in Europe). Participants (n = 36) were taking daily oral OAT (methadone or buprenorphine) or using heroin daily without OAT. They included 26 men and 10 women, aged 24-63 years. All were asked for their views on weekly, monthly, and six-monthly duration buprenorphine. Responses were audio-recorded, transcribed, and analyzed by Iterative Categorization. Results Participants generally stated that having buprenorphine of different prolonged durations was positive. They tended to believe that 'longer' prolonged-release formulations would be beneficial for patients who wanted to avoid thinking about drugs and drug-using associates, wished to evade the stigma of substance use, and desired 'normality' and 'recovery.' In contrast, participants favored 'shorter' prolonged-release formulations for patients who are new to OAT, worried about the safety and reliability/effectiveness of OAT, want a 'break' from street opioids, and need contact with services to monitor/support them. Participants indicated that transitioning between OAT medications of different duration would be a very individual process. Some also linked prolonged-release OAT duration to political, philosophical, and ethical issues, such as patient coercion and mental capability. Conclusions Medication duration is an important but complex feature of prolonged-release buprenorphine, with patients' views and preferences likely to be influenced by a wide range of factors. We need further qualitative research to explore the experiences of people who have actually used prolonged-release OAT. Meanwhile, drug developers should continue to build flexibility and choice into OAT products to ensure that future treatment is acceptable to patients and able to accommodate their diverse individual needs.